The establishment of religious confessions in China - Smagulova К (Journal of Oriental Studies, 2016)
This article analyses the investigation of the aspects of the systems of acknowledging, understanding, changing and developing the world, that were formed and witnessed by the societies of different levels and types. This is the exploration of such facts as those systems were founded based on certain methods and approaches, on traditional basics, as the importance of living, world-knowing, thinking methods for the social-ethnic societies, as those systems have not lost their influence and power yet neither in the modern informational world nor along the stages of historical evolution. Here is given a determination of a stable preservation of historically founded traditions, style of world cognition and its expression in art, in the roots of those ethnicities’ sense and their value as the part of the world’s spiritual establishment.